EVOLUTION AND OPTIMIZATION OF ACTIVITY-BASED COSTING FOR STRATEGIC COST MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Dhimas Haricahyo; Andry Arifian Rachman (Universitas Tulungagung, 2026)
This article examines the development of Activity-Based Costing (ABC) and its optimization in supporting Strategic Cost Management (SCM). The study applies a Systematic Literature Review (SLR) based on the PRISMA 2020 procedure. Scopus was used as the main database, while Google Scholar was used to identify relevant national articles selected through SINTA 1 and SINTA 2 indexation criteria. At the identification stage, 122 records were collected. After the screening and eligibility process, 59 articles met the inclusion criteria and were analyzed using narrative synthesis and thematic analysis. The synthesis indicates that ABC implementation is still shaped by several practical challenges, including activity complexity, detailed data requirements, resource availability, technical capability, and organizational resistance. However, ABC has also developed into more flexible and applicable forms, such as Time-Driven Activity-Based Costing, Duration-Based Costing, hybrid costing, ERP/SAP integration, and digital information systems. In the context of SCM, ABC strengthens cost information by improving overhead allocation, profitability analysis, cost control, performance evaluation, and managerial decision-making. Therefore, ABC should not be viewed merely as a cost allocation technique, but as a strategic cost information system that supports managerial and organizational decisions